Parental involvement in the clinical practice of the MEII methodology - Raymundo, Lais Soares; Almeida, Andressa de Oliveira (Seven Editora, 2023)
Objective: Expose the practice of a transdisciplinary team that includes parental practice and parental psychological support in its own methodology of therapeutic intervention. These spheres are part of parental involvement, which is one of the pillars of such methodology. Report:The experience that will be reported takes place in the model clinic of the Intensive Integrated Stimulation Method - MEII, which is located in the city of Petrópolis-RJ. The method aims to develop work with the families/caregivers of its patients, as it recognizes that their participation, commitment, and well-being are essential for the success of the interventions. Final considerations: According to the experience gained in the practical application of the MEII methodology's model clinic, it is possible to observe better results with patients whose family members and caregivers engage in the proposal of parental involvement. As they come to better understand diagnoses, prognoses, postural and behavioral management, developmental phases, among other aspects that assist in daily practice, as well as receive psychotherapeutic listening to help with their life issues, they become contributors to the therapeutic process. DOI:https://doi.org/10.56238/sevened2023.006-084